MULTIPLE-CHOICE CLASSIFICATION IN AIR NAVIGATION SYSTEM - Kharchenko, Volodymyr P.; Ostroumov, Ivan V. (Proceedings of National Aviation University, 2008)
In this article a multi-choice approach for aircraft deviation control from the flight-planned trajectory has been represented. Nine air-situation classes are considered as optimal number for guarantied required safety level. Bayesian classifier has been used for air-situation classification.